The likelihood of divorce and the riskiness of financial decisions. (September 2019) - Stark, Oded; Szczygielski, Krzysztof
Abstract: We link causally the riskiness of men's management of their finances with the probability of their experiencing a divorce. Our point of departure is that when comparing single men to married men, the former manage their finances in a more aggressive (that is, riskier) manner. Assuming that single men believe that low relative wealth has a negative effect on their standing in the marriage market and that they care about their standing in that market more than married men do, we find that a stronger distaste for low relative wealth translates into reduced relative risk aversion and, consequently, into riskier financial behavior. With this relationship in place we show how this difference varies depending on the "background" likelihood of divorce and, hence, on the likelihood of re-entry into the marriage market: married men in environments that are more prone to divorce exhibit risk-taking behavior that is more similar to that of single men than married men in environments that are little prone to divorce. We offer a theoretical contribution that helps inform and interpret empirical observations and regularities and can serve as a guide for follow-up empirical work, having established and identified the direction of causality.